Comparison of early outcome of stapler versus hand sewn closure of duodenal stump after gastrectomy in gastric cancer - Mahmud, Muhammad Khaled; Choudhury, Jalal Ahmed; Mahmud, Akbar Neaz; Rashedul Islam, M. (International Journal of Research in Medical Sciences, 2025)
Background: Gastric cancer (GC) remains a major global health challenge, ranking as the fifth most common malignancy and the fourth leading cause of cancer-related death worldwide. Surgery with gastrectomy remains the mainstay of curative treatment, but duodenal stump leakage (DSL) continues to be one of the most feared postoperative complications, associated with high morbidity and mortality. The choice between stapled and hand-sewn duodenal stump closure remains a debated topic, especially in resource-limited regions such as South Asia, where cost and accessibility are critical factors. The study aimed to compare the early outcomes of stapler versus hand-sewn closure of the duodenal stump after gastrectomy in gastric cancer patients. Methods: This prospective comparative study included 40 gastric cancer patients undergoing elective gastrectomy, divided into stapler (n=20) and hand-sewn (n=20) duodenal stump closure groups. The study was conducted at Sylhet MAG Osmani Medical College and Hospital, Sylhet, Bangladesh, from July 2024 to June 2025. Patients with ASA class III–IV or prior neoadjuvant chemotherapy were excluded. Standardised operative and postoperative protocols were followed, and outcomes assessed included operative time, closure time, complications, hospital stay, and cost. Data were analysed using statistical package for the social sciences (SPSS) 26 with t-test, Chi-square, and multivariable logistic regression, considering p<0.05 as significant. Results: Both groups were comparable in baseline demographics and type of gastrectomy. Stapler closure significantly reduced operative time (158±22 versus 177±25 min, p=0.007) and stump closure time (9±3 versus 18±5 min, p<0.001). Early postoperative complications, including duodenal stump blowout, were slightly lower in the stapler group but not statistically significant. Recovery was faster with stapler closure, with earlier oral intake (2.7±0.9 versus 3.8±1.2 days, p=0.009) and shorter hospital stay (8.2±2.0 versus 10.1±2.5 days, p=0.026). Stapler procedures incurred higher costs (p=0.01). Conclusion: Stapled duodenal stump closure after gastrectomy offers faster surgery, earlier recovery, and shorter hospital stay than hand-sewn closure, without added complications. Despite higher costs, it represents a safe and effective option in selected gastric cancer patients.